1987
DOI: 10.1139/x87-212
|View full text |Cite
|
Sign up to set email alerts
|

Top pruning Douglas-fir seedlings: morphology, physiology, and field performance

Abstract: Seedlings from nine Douglas-fir (Pseudotsugamenziesii (Mirb.) Franco) seed sources were top pruned at six nurseries in the Pacific Northwest and then planted at field sites in their own seed zones and on one common site. Seedlings pruned tall (25 cm) and early in the growing season flushed again about 5 weeks after pruning and set bud 2 weeks later than unpruned controls. Nursery yield (number of shippable seedlings) was the same for tall–early pruned and control seedlings; however, pruning increased the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many of those studies evaluated whether shoot pruning was necessary to aid the transplant process by compensating for root loss that occurs when plants were dug from a field. Most studies concluded that various measures of growth were unchanged, and survival was identical, whether pruned or not at planting (e.g., Shoup et al 1981;Evans and Klett 1984;Hummel and Johnson 1986;Duryea and Omi 1987;Chandler 1990). Compared to not pruning, crown size was generally similar or less on pruned trees one to several years after planting.…”
mentioning
confidence: 99%
“…Many of those studies evaluated whether shoot pruning was necessary to aid the transplant process by compensating for root loss that occurs when plants were dug from a field. Most studies concluded that various measures of growth were unchanged, and survival was identical, whether pruned or not at planting (e.g., Shoup et al 1981;Evans and Klett 1984;Hummel and Johnson 1986;Duryea and Omi 1987;Chandler 1990). Compared to not pruning, crown size was generally similar or less on pruned trees one to several years after planting.…”
mentioning
confidence: 99%
“…For example, proper top-pruning of loblolly pine seedlings (months prior to lifting) controls height growth, can increase freezing tolerance [130] and increases the probability of higher field survival after outplanting [101]. In contrast, top-pruning of Douglas-fir effectively controls shoot height [98], but it can delay bud development and result in the reflush of lateral buds [131] which might result in fall frost damage. Root wrenching is another practice used to create stress and thus harden bareroot seedlings during latter stages of seedling development.…”
Section: Cultural Practicesmentioning
confidence: 99%
“…One of the first was a survival and growth comparison of conifer species native to the Hemlock Experimental Forest in Gray's Harbor County, Washington (Worthington 1955). Among many other trials, plantings were made to evaluate timing effects of lifting or planting, and the influence of various nursery practices on seedling field performance (Duryea and Omi 1987, Jenkinson and others 1993, Owston and others 1986, Stein 1988, Strothmann 1971, Tanaka and others 1976, Walters and Soos 1961, Winjum 1963. Other plantings investigated the effect of seedling size and supplemental treatment on subsequent field performance (Edgren 1977, Newton and others 1993, Strothmann 1980, Van den Driessche 1992, Walters and Kozak 1965.…”
Section: Direct Seedingmentioning
confidence: 99%